Ignition of the wood biomass particles under conditions of near-surface fragmentation of the fuel layer. (15th September 2019) - Kuznetsov, G.V.; Syrodoy, S.V.; Gutareva, N.Y.; Kostoreva, A.A.; Kostoreva, Zh.A.
Highlights: Experimental studies of the ignition of wood particles with a dispersed surface. We found that as a result of surface dispersion, the rate of ignition increases. We developed a mathematical model of the process of ignition of particles of wood. Theoretical and experimental results showed good agreement. Abstract: The results of the experimental and theoretical studies of the ignition processes of the woody biomass single particles of a cubic form under conditions of preliminary fragmentation of the particle surface have been presented. It is established experimentally that the increase in the result of the external mechanical influences, in the heat exchange area (due to the formation of grooves and cracks) leads to an acceleration of the ignition process. According to the results of the experiments, a new mathematical model of the ignition process of the wood biomass particle under conditions of near-surface fragmentation, which differs from previously known ones, has been formulated. It describes the thermophysical processes and thermochemical processes and intense phase (evaporation of water) transformations, in conditions of change in the surface relief of the particle, and, accordingly, the density of the heat flux along the particle contour and the concentration of combustible gases in the boundary layer of the particle. The formulated system of the nonlinear partial differential equations in partial derivatives with the corresponding boundary conditions describes the process of ignition in a two-dimensional setting, taking into account the substantial nonuniformity of the temperature field of a wood particle in the induction period. Up to the present time, the mathematical models of such a degree of detailing of the physical processes occurring together during the ignition of wood under the conditions of fragmentation of its surface have not been formulated. The comparative analysis of the ignition delay times (tign ), obtained theoretically and experimentally, has showed their satisfactory correspondence. As a result of the numerical simulation, the temperature fields in the "fuel particle-high-temperature medium" system have been obtained, illustrating the features of the course of the thermochemical reactions of the wood particles ignition under conditions of fragmentation of their surface.